Pemberian Diet Tinggi Protein dan Energi pada Pasien Covid-19 dengan Pneumonia: Sebuah Laporan Kasus - Adelia Dwi Setiyani; Stefania Widya Setyaningtyas; Yuyun Erlina (Media Gizi Kesmas, 2024)
Background: The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is the causative agent of the infectious disease known as Coronavirus Disease 2019 (COVID-19). This virus is a novel strain of virus that has never been discovered in humans before. A history of diseases such as pneumonia can also raise the likelihood of experiencing hazardous complications, one of which is acute respiratory distress syndrome (ARDS). An additional risk factor includes having a history of the condition. The Standardized Nutrition Care Process (SNCP) is carried out for patients by providing a high energy, high protein diet (HEHP) to meet the patient's needs. Objectives: Knowing the management of standardized nutritional care for patients by providing a high protein and energy diet to patients confirmed for COVID-19 with a history of pneumonia. Methods: A case study was conducted in February 2021 in patients at Dr. Soetomo hospital, Surabaya. Sampling has been determined in advance by the hospital nutritionist and internship guide according to the case criteria. The data collection method is carried out with observation and analysis over 3 days in the field of intake, physical/clinical, biochemical and anthropometry domains. The researchers also conducted literature studies to complete complete the required data. Results: The results of the monitoring and evaluation showed that the laboratory results had fluctuating changes, the results were changes in the type of food and the method of administration that was given, the physical and clinical conditions had begun to improve, despite the fact that there were still complaints of shortness of breath, and the patient's intake increased from day to day, and there were several fulfillments of macronutrients that reached the target (<80%). Conclusions: The patient's recovery condition was not satisfactory; the results of the physical/clinical and biochemical monitoring from day to day showed that it continued to show fluctuating changes. However, after monitoring the patient for three days, it was discovered that the patient's food intake had increased from liquid food to soft food and had met the daily needs targets that had been predetermined.